GAMBARAN PENGETAHUAN PASIEN SWAMEDIKASI TERHADAP BEYOND USE DATE (BUD) OBAT DI APOTEK X CIKARANG - Pratiwi, Desi Eka; Haifa, Ayu Izzatin; Amalia, Tisa; Marliana, Elsa (Politeknik META Industri Cikarang, 2024)
The expiry time of a drug or expiry date is the time limit for using a drug after it is produced by a pharmaceutical factory, before the packaging is opened. Drug ED is a condition at a time where a drug is no longer suitable for use starting from the potency, quality, efficacy and safety of the drug. The expiration date of a drug is determined when the drug is first opened, which is called the Beyond Use Date (BUD). BUD is the time limit for using a medicinal product after it has been formulated or prepared or after the primary packaging has been opened or damaged. The aim of this study was to determine the level of knowledge of BUD drug self-medication patients. The method used is a survey method by giving a questionnaire with 20 questions to respondents. Based on the research results, it was found that the level of knowledge of self-medication patients was in the good category for semi-solid preparations with a percentage of (78.98%), solid preparations (63.78%), liquid preparations (67.02%) while for knowledge of BUD medicines with a percentage (75.26%). Based on the results of the study it can be concluded that the patient's level of knowledge is still in the sufficient category with a percentage (75.26%). Keywords : level of knowledge, BUD, ED